The Influence of Attitude, Ethos Work and Commitment on Work Effectiveness (Census of Civil Servant BPMKB Tasikmalaya Regency) - Sulaeman, Maman; Andriani, Sandi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2018)
ABSTRACT   This research is based on the problems that occur in the Community Empowerment and Family Planning (BPMKB) Tasikmalaya that the effectiveness of work is still low can be seen from the lack of optimizing self potential as in the reporting is not completed on time. This study aims to analyze the influence of attitude, work ethic and commitment to the effectiveness of employment in BPMKB Tasikmalaya District. The method used is quantitative with path analysis, which is to get the picture, relationship pattern and influence of research variables that have been determined. The result of the research shows that there is significant influence of employee attitude, work ethic, and commitment to work effectiveness equal to 0,691 or 69,1% and p-value 0,000 <0,05. Thus the hypothesis accepted that there is influence of employee attitudes, work ethic, and commitment to Work Effectiveness. Based on these conclusions, it is advisable for the leadership to provide sanctions to employees who are not timely in reporting, Employees can provide services to the public and be open to colleagues and bosses about matters relating to the work Keywords: Attitude, Work Ethic, Commitment, Work Effectiveness